Determination of Histamine in Silages Using Nanomaghemite Core (γ-Fe₂O₃)-Titanium Dioxide Shell Nanoparticles Off-Line Coupled with Ion Exchange Chromatography - Cernei, Natalia; Lackova, Zuzana; Guran, Roman; Hynek, David; Skladanka, Jiri; Horky, Pavel; Zitka, Ondrej; Adam, Vojtěch (International journal of environmental research and public health, 2016)
The presence of biogenic amines is a hallmark of degraded food and its products. Herein, we focused on the utilization of magnetic nanoparticles off-line coupled with ion exchange chromatography with post-column ninhydrin derivatization and Vis detection for histamine (Him) separation and detection. Primarily, we described the synthesis of magnetic nanoparticles with nanomaghemite core (γ-Fe₂O₃) functionalized with titanium dioxide and, then, applied these particles to specific isolation of Him. To obtain further insight into interactions between paramagnetic particles' (PMP) surface and Him, a scanning electron microscope was employed. It was shown that binding of histamine causes an increase of relative current response of deprotonated PMPs, which confirmed formation of Him-PMPs clusters. The recovery of the isolation showed that titanium dioxide-based particles were able to bind and preconcentrate Him with recovery exceeding 90%. Finally, we successfully carried out the analyses of real samples obtained from silage. We can conclude that our modified particles are suitable for Him isolation, and thus may serve as the first isolation step of Him from biological samples, as it is demonstrated on alfalfa seed variety Tereza silage.
Keywords: Biogenic Amines; Silage; železité sloučeniny; Histamine; siláž; biogenní aminy; histamin; chromatografie iontoměničová; titan; Ferric Compounds; Nanoparticles; Chromatography, Ion Exchange; Titanium; nanočástice